2001
DOI: 10.1248/cpb.49.282
|View full text |Cite
|
Sign up to set email alerts
|

Bufadienolides and a New Lignan from the Bulbs of Urginea maritima.

Abstract: Thirty three compounds were obtained from the bulbs of Urginea maritima (Liliaceae). The compounds were identified by means of fast atom bombardment mass spectrometry (FAB-MS), nuclear magnetic resonance ( 1 H-NMR), ( 13 C-NMR), nuclear overhauser effects (NOE) and two dimensional (2D) NMR. Ten of them were new natural compounds. Nine were bufadienolides and only one was lignan in these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 17 publications
0
44
0
1
Order By: Relevance
“…25) Plant Material The roots of Asclepias syriaca L. (No. 2380M) were collected from the botanical garden of the University of Shizuoka in Japan in September, 1998 and identified by Prof. T. Noro.…”
Section: Methodsmentioning
confidence: 99%
“…25) Plant Material The roots of Asclepias syriaca L. (No. 2380M) were collected from the botanical garden of the University of Shizuoka in Japan in September, 1998 and identified by Prof. T. Noro.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained known aglycones were identified as cynajapogenin A (1a), 1,2) glaucogenin-A (2a), 3,4) 2a-hydroxyanhydrohirundigenin (12a) 5) and atratogenin A (18a) 2) in view of the 1 H-and 13 C-NMR spectroscopic data. The acquired sugar mixtures were fractionated to cymarose, digitoxose and a mixture of oleandrose and sarmentose using silica gel column chromatography.…”
mentioning
confidence: 99%
“…In the 1 H-and 13 C-NMR spectra of 1, one anomeric proton and carbon signals were observed at d 5.45 (1H, dd, Jϭ9.5, 2.0 Hz)] and d 98.3, in addition to signals due to the aglycone, which was identified as a 13,14-seco-type pregnane, cynajapogenin A (1a) by acid hydrolysis with 0.1 M H 2 SO 4 . The 13 C-NMR spectral comparison of 1 with 1a showed that glycosylation shifts were presented at the C-2, -3 and -4 positions [C-2 (Ϫ2.2 ppm), C-3 (ϩ9.1 ppm), C-4 (Ϫ2.8 ppm)]. 6) Thus, 1 was glycosylated at the C-3 position, and was considered to be cynajapogenin A 3-O-monoglycoside.…”
mentioning
confidence: 99%
“…23) Extraction and Isolation The aerial part of Baccharis dracunculifolia DC. (644 g) was extracted three times with MeOH under reflux.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular formulae of dracunculifosides G-I (23-25) were considered to be C 23 This data led us to conclude that the aglycone moiety of 24 was benzyl alcohol. This was confirmed by acid hydrolysis.…”
mentioning
confidence: 99%